Platelets at the Crossroads of Cancer: Activating Epithelial Mesenchymal Transition in Colorectal Carcinogenesis via Snail1 - Syarifuddin, Erwin; Lusikooy, Ronald Erasio; Masadah, Rina; Raharjo, Warsinggih; Cangara, Husni; Zainuddin, Andi Alfian; Mulyawan, Made; Aryanti, Citra (Asian Pacific Journal of Cancer Biology, 2025)
Introduction: Epithelial-mesenchymal transition (EMT) was an important process in colorectal cancer progression. Activated platelets and thrombocytosis had been associated with cancer progression, but the specific mechanism in triggering EMT through the transcription factor Snail1 was not fully understood. Methods: This study used an observational analytical design with a cross-sectional approach. The subjects were colorectal cancer patients who underwent blood tests to determine platelet and activated platelet levels (P-selectin) and tissue to determine Snail1 and EMT transcription factors (E-cadherin and vimentin). Statistical analysis was performed using SPSS, Python, and Google Colab. Results: This study showed a significant role of activated platelets in triggering EMT (p = 0.005), activated platelets in triggering Snail1 (p = 0.042), and Snail1 in triggering EMT (p = 0.002). Causality assessment by artificial intelligence analysis of direct acyclic graphs and Granger causality tests showed that changes in platelet activation levels significantly preceded increased Snail1 expression, which in turn was followed by increased EMT markers. In addition, a decision tree was built to predict EMT from P-selectin and Snail1 levels with an accuracy of 62%. Conclusion: There was no significant relationship between thrombocytosis and activated platelets, and no significant role of thrombocytosis in EMT was found. Thus, the results of this study indicated a significant role of activated platelets in triggering EMT through the transcription factor Snail1 in colorectal cancer.